Autoethnography: A Method of Research and Teaching for Transformative Education - Belbase, Shashidhar; Luitel, Bal Chandra; Taylor, Peter Charles (Journal of Education and Research, 2008)
This paper discusses the thesis that autoethnography as tool in research provides the researcher to examine his or her pedagogical and research practices from his or lived evocative experiences. The essence of this paper is to seek the possibilities of linking autoethnography as a method of inquiry that catalyses the transformative pedagogy positively in mathematics education. It is an outcome of my dissertation of Masters of Philosophy (M.Phil.) in Education. I highlights the importance of autoethnography in research in a way that permits researchers to apply flexible modes of inquiry from their life experiences with motives of change to take place in educational institutions and classroom practices. DOI: http://dx.doi.org/10.3126/jer.v1i0.7955 Journal of Education and Research 2008, Vol. 1, No. 1, pp. 86-95